Transformation the Coordinates From Global Geodetic Datum WGS84 to Local One in Syria Using Stepwise Multiple Regression Technique - محفوض, ندى (Latakia University Journal -Engineering Sciences Series, 2022)
The most modern practical application of coordinate transformation has appeared with the advent of global positioning system by satellite. In this research, the accuracy of the coordinates of points resulting from the use of the stepwise multiple regression technique to transformation from the global geodetic datum (WGS84) to local one in Syria (clarck1880) was assessed by comparing them with the real coordinates of these points measured by the total station instrument, in addition to comparing its with the accuracy of the coordinates produced from the mobile topographic application located on the smartphone, which depends on the seven transformation parameters of Deir ez-Zor. The results were presented in tables and charts, and indicated that the coordinates resulting from the use of the stepwise multiple regression equation are better than the accuracy of the coordinates using Deir ez-Zor Parameters so that the average positional error (1,100) meters instead of (4,030) meters.